Multimedia Learning to Improve Learning Outcomes and Activity of Students in Culinary Education - Rahman, Luthfi Riyadh (PT. Publikasiku Academic Solution, 2024)
This study aims to: (1) produce learning multimedia for culinary education students; (2) determine how far learning multimedia improves student learning outcomes; and (3) determine how far learning multimedia increases student activity. The method used is research and development (R&D), with reference to the development steps of Alessi and Trollip. The test subjects of this study consisted of an alpha test and a beta test. Data collection on learning outcomes was carried out by giving pre- and post-tests, while activeness data was carried out by assessing student activity when using multimedia questionnaires. The results showed that: (1) multimedia products in the criteria were very suitable for use in terms of aspects of material assessment and media assessment; (2) learning multimedia increased student learning outcomes with an achievement percentage from 5% (pre-test) to 91.5% (post-test); and (3) learning multimedia increases student activity by 66.90% with high criteria.